Acute compartment syndrome due to skeletal muscle metastases from poorly differentiated upper gastrointestinal adenocarcinoma: a case report - Richard Gentry; Prince Mohan Anand; Ahmed I Kamal; Ahmad Saleh Alqassieh; Ammar Obaid Mahmood; Mesrop Ayrapetyan; Monther Saud Amer Altiti (World Journal of Surgical Oncology)
Abstract Background Acute compartment syndrome (ACS) is characterized by increased pressure within the fascial network of any muscle, leading to impaired circulation and potential myonecrosis. Very rarely, soft tissue infiltration by metastatic disease can cause localized swelling that increases intercompartmental pressures. We report an unusual case of invasive, poorly differentiated upper gastrointestinal adenocarcinoma presented by acute compartment syndrome of the lower extremity and subsequent acute kidney injury (AKI) caused by myonecrosis-induced cast nephropathy. Case Presentation A 52-year-old male presented to the hospital with rapid onset unilateral right leg pain and tense edema accompanied by myonecrosis with no explicable etiology complicated by AKI. Surgical fasciotomy and subsequent muscle biopsy yielded poorly differentiated non-small cell adenocarcinoma. CT imaging identified diffuse adenopathy along with abnormal thickening of the distal esophagus, gastroesophageal (GE) junction, and gastric cardia. Further investigation via upper esophagogastroduodenoscopy (EGD) revealed an exophytic mass in the distal esophagus extending into the stomach. This lesion was confirmed via biopsy as primary invasive poorly differentiated upper gastrointestinal (UGI) adenocarcinoma. Conclusion This case highlights the need for clinicians to implement high-risk screening for UGI cancers and consider skeletal muscle metastasis as a cause of nontraumatic ACS. It emphasizes the importance of interdisciplinary collaboration in managing such complex cases and the role of timely surgical and oncological intervention in preventing long-term complications of ACS. Furthermore, it highlights the potential use of more efficient and specific MR imaging techniques to diagnose ambiguous cases of ACS.